Rancang Bangun Mouse untuk Penyandang Disabilitas Menggunakan Sensor MPU-6050 dengan Metode Kalman Filter sebagai Peredam Noise - Putri Ayu Zartika; Mila Kusumawardani; Koesmarijanto Koesmarijanto (Jurnal Jaringan Telekomunikasi, 2021)
Problems that are often faced by people with physical disabilities are those who have limited hands, one of which is when they will use the computer. His inability to grip and use the mouse is often a barrier in using the computer. The purpose of the design of the tool is to provide facilities for people with disabilities to be able to use a mouse that will be moved based on head movements without noise interference caused by the MPU-6050 sensor. The results of the tests carried out show that designing a mouse with the MPU-6050 sensor has been successfully carried out, the MPU-6050 sensor by implementing a kalman filter as a noise reducer on the X axis has an accuracy value with an average error percentage of 0.09% and at Y angle is 0.12%. Data transmission from the mouse to the computer is done wirelessly using bluetooth HC-05 can receive data well as far as 12.5 meters with an error percentage of 0%. The button on the mouse that functions to perform the left click function when the button is bitten 1x, right click when the button is bitten 2x and click and hold to do a left click 2x or double click can run according to the command, has a 100% success rate.